Spatially and cell-type resolved quantitative proteomic atlas of healthy human skin - Beatrice Dyring-Andersen (Nature Portfolio, 2020)
The human skin is a highly complex organ comprising multiple tissue layers and diverse cell types. Here, the authors present a spatially-resolved quantitative proteomic atlas of the healthy human skin, characterizing the protein profiles of four skin layers and nine cell types.